The Land of Oz as World Literary and Cultural Heritage - Haramija, Dragica (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
The article discusses the Land of Oz created by Lyman Frank Baum who, be-tween 1900 and 1920, published the famous series of books for children, which included fourteen works. The latter belong to so-called fantasy fiction, where the boundary between the real world and fantasy is precisely outlined and the main literary character, Dorothy, is aware of her transition from the real world to a parallel fantasy one with its own laws and literary characters (the inhabitants of various lands, the good and evil witches, Dorothy’s new friends). The most suc-cessful book of the series, The Wonderful Wizard of Oz (1900), was illustrated by William Wallace Denslow, and its first Slovene edition came out in 1959. In it, Dorothy, the Scarecrow, the Tin (Wood)man and the Cowardly Lion expose an old man, namely the fake wizard, and successfully overcome all obstacles by working together and through their friendship. The work is considered a children’s classic all over the world, promoting ideas of positive values: thoughtfulness, boldness, courage and longing for home.